Seismic protection of storage rack systems with base isolation - Yahya, Mir Mohammad Amer (İstanbul Kültür Üniversitesi / Lisansüstü Eğitim Enstitüsü / İnşaat Mühendisliği Ana Bilim Dalı / Yapı Bilim Dalı, 2020)
Çelik raf sistemleri, depolar ve mağazalar gibi halka ve çalışanların erişimine açık yerlerde farklı tipte ürünleri depolamakta yaygın olarak kullanılmaktadır. Bu sistemlerin yapısal bileşenleri, burkulmaya maruz olabilecek ince cidarlı açık kesitli çelik elemanlardan oluşmaktadır ve bu sistemlere etkiyen hareketli yükler sistemin zati ağırlığından oldukça büyük olabilmektedir. Bu sebepler çelik raf sistemlerinin deprem yükleri etkisi altında analizini ve boyutlandırılmasını güçleştirmektedir. Buna ek olarak, bu sistemlerin deprem etkisiyle hasar görmesi, depolanan ürünlere gelebilecek hasarlar veya hizmetleri aksamasına bağlı oluşacak ekonomik kayıplara ek olarak çalışanların ve müşterilerin yaralanmaları veya ölümüne neden olabilmektedir. bu makalede, depolama raflarının tabanında Tek Sürtünme İzolatörlerinin kullanımı yapılmıştır. Yalıtılmış rafın yer değiştirmesi ve hızlanması sabit tabanlı rafla karşılaştırıldı. Ayrıca, 6 uzak saha ve 6 yakın saha depreminde farklı yükleme türlerinde raf yapısının davranışı gözlenmiştir. Raf yapısı SAP2000 ticari yazılımı kullanılarak modellenmiştir ve sonuçlar sunulmuştur.

Steel storage rack systems are widely used in warehouses and stores for storing different types of products accessible for public and employees. Structural components of these systems consist of slender, thin-walled open section steel members, which are quite susceptible to buckling, and the live loads acting on these structures are much greater than the self-weight of these structures. These issues complicate the design and analysis of steel storage racks under earthquake loads. In addition, failure of these systems during earthquakes can result in the loss of lives of employees and customers in addition to economic losses due to damages to stored products and disruption of services. This study investigates the use of base isolation to improve the seismic response of steel storage racks. Seismic isolation system consists of friction pendulum bearings that support the floor slab underneath the storage racks. The model geometry and the loads supported by the steel storage rack has been adapted from the Seisracks 2 project. Finite element model of the fixed base storage racks was created using SAP 2000 and calibrated with the experimental results from the Seisracks 2 project. A parametric study which covered the variation of friction coefficients and distribution of live loads was conducted with a suite of 12 earthquakes to investigate the reductions in rack accelerations and drifts as well as the changes in bearing displacements. Results of the parametric study indicate that seismic isolation was effective for reducing the response parameters and distribution of live load as well as the friction coefficient of bearings can have a significant influence on the seismic response.
Depolama raf sistemlerinin sismik izolasyonla depremden korunması
Keywords: İnşaat Mühendisliği; Civil Engineering